The inter- and intra- generational transmission of family poverty and hardship (adversity): A prospective 30 year study - Najman, J.; Bor, W.; Ahmadabadi, Z.; Williams, G.; Alati, Rosa; Mamun, A.; Scott, J.; Clavarino, A. (Public Library of Science, 2018)
© 2018 Najman et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Background Children exposed to family poverty have been found to have higher morbidity and mortality rates, poorer mental health and cognitive outcomes and reduced life chances across a wide range of life domains. There is, however, very little known about the extent to which poverty is experienced by children over their early life course, particularly in community samples. This study tracks changes in family poverty and the main factors that predict family poverty (adverse life experiences) over a 30-year period since the birth of the study child. Methods Data are from a prospective, longitudinal, birth cohort study conducted in Brisbane, Australia. Consecutive families were recruited at the mothers’ first obstetrical visit at one of two major obstetrical hospitals in Brisbane. Data are available for 2087 families with complete data at the 30-year follow-up. Poverty was measured using family income at each time point (adjusted for inflation). Findings Poverty affects about 20% of families at any time point. It is common for families to move in and out of poverty, as their circumstances are affected by such adversities as unemployment and marital breakdown. Over the period of the study about half the families in the study experienced poverty on at least one occasion. Only a very small minority of families experienced persistent poverty over the 30-year duration of the study. Logistic regressions with time lag show that family poverty predicts subsequent adversities and adverse events predict subsequent poverty. Conclusions Experiences of poverty and adversity are common and may vary greatly over the child’s early life course. In assessing the health consequences of poverty, it is important to distinguish the timing and chronicity of early life course experiences of poverty and adversity.